Growing without a mother results in poorer sexual behaviour in adult rams. (11th July 2017) - Damián, J.P.; Beracochea, F.; Machado, S.; Hötzel, M.J.; Banchero, G.; Ungerfeld, R.
Abstract : The aim of this study was to determine if the absence of the mother during rearing has long-term effects on sexual behaviour and physiological reproductive parameters of adult rams. Two groups of rams were: (1) artificially reared, separated from their dams 24 to 36 h after birth (Week 0) and fed using sheep milk until 10 weeks of age (group AR, n =14); and (2) reared by their dams until 10 weeks of age (group DR, n =13). Sexual behaviour (tests of 20 min) and physiological reproductive parameters were analysed separately for the non-breeding (Weeks 42 to 64) and the breeding (Weeks 66 to 90) seasons. Body weight, scrotal circumference, gonado-somatic index, testosterone concentrations or sperm parameters were similar in both rearing conditions (AR v . DR) in both seasons. During the non-breeding season AR rams displayed fewer ano-genital sniffings (AR: 4.2±0.4 v . DR: 5.3±0.4, P =0.04) and matings (AR: 1.2±0.2 v . DR: 1.8±0.2, P =0.002) than DR rams. During the breeding season AR rams displayed fewer ano-genital sniffings (AR: 4.3±0.5 v . DR: 5.7±0.5, P =0.005), flehmen (AR: 0.7±0.2 v . DR: 1.1±0.2, P =0.03), mount attempts (AR: 1.4±0.2 v . DR: 2.1±0.2, P =0.04), and tended to mount less frequently (AR: 6.6±0.9 v . DR: 8.8±0.9, P =0.08) than DR rams. In conclusion, the absence of the mother during the rearing period negatively affected display of sexual behaviour towards oestrous ewes during a rams adult life in both breeding and non-breeding seasons. However, it did not affect testis size, testosterone secretion or sperm variables.